2014
DOI: 10.1080/09540121.2014.920949
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes in HIV-exposed-uninfected children versus those not exposed to HIV

Abstract: Human immunodeficiency virus (HIV)-negative children born to HIV-infected mothers may exhibit differences in neurodevelopment (ND) compared to age- and gender-matched controls whose lives have not been affected by HIV. This could occur due to exposure to HIV and antiretroviral agents in utero and perinatally, or differences in the environment in which they grow up. This study assessed neurodevelopmental outcomes in HIV-exposed uninfected (HEU) and HIV-unexposed uninfected (HUU) children enrolled as controls in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 16 publications
(22 reference statements)
4
59
3
Order By: Relevance
“…This study complements prior reports of no detectable differences in neurodevelopment between HEU and HUU children 13 . Our previous findings in the full sample (not only imaged children) demonstrated small, although statistically significant group differences in neuropsychological test performance 14, 15 ; our current study mapping the neuropsychiatric scores across the brain enables us to observe the neuroanatomical pathways where these group differences may reside. However, the clinical significance of our previous findings remains unclear.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This study complements prior reports of no detectable differences in neurodevelopment between HEU and HUU children 13 . Our previous findings in the full sample (not only imaged children) demonstrated small, although statistically significant group differences in neuropsychological test performance 14, 15 ; our current study mapping the neuropsychiatric scores across the brain enables us to observe the neuroanatomical pathways where these group differences may reside. However, the clinical significance of our previous findings remains unclear.…”
Section: Discussionmentioning
confidence: 61%
“…School attendance was unavailable for two children (1 HEU and 1 HUU), caregivers’ education level was unavailable for three children (2 HEU and 1 HUU), and caregiver income was unavailable for two children (1 HEU and 1 HUU). All children completed age-appropriate neuropsychological assessments as previously described 14, 15 . The battery included: the Wechsler Preschool and Primary Scale of Intelligence-III (WPPSI-III, ages 2 to 6 years) and the Wechsler Intelligence Scale for Children (WISC-III, ages 6 to 17 years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study within PHACS also evaluated cognitive outcomes in older HEU children and did not find associations between any perinatal ART class regimens and cognitive and academic scores [84]. One study from Thailand reported small reductions in Wechsler Intelligence Scale testing comparing HEU to HUU children but acknowledged the uncertainty around the long-term clinical significance of these findings [108]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, HEU children were found to be more likely to experience motor impairment (14%), delays in expressive language, and fine motor problems. 16 These impairments could be due to perinatal exposure to the HIV virus or antiretroviral therapy (ART), 17, 18 For instance antenatal HIV-exposure (without infection) may compromise HEU children’s cognitive development, when maternal immune activation negatively affects the developing fetal brain. 19 …”
Section: Introductionmentioning
confidence: 99%